Regional Industry in the Digital Era: Information and Communication Dimension - Urasova, Anna Alexandrovna (Economy of Regions, 2019)
In the digital era in Russia, there is a need for the regional industry’s accelerated development. I aimed to assess the process of the mutual influence of information and communication technologies (as a tool for the digital environment’s formation) on production processes in the Russian Federation regions. For that purpose I built a correlation model that allows identifying and characterizing the relationships between the studied processes. I hypothesised that the regions industrial production (the resulting figure) depended on the cost of information and communication technologies (the studied factor). Accordingly, the study is based on the economic and mathematical modelling of empirical spatial data of the Russian official statistics, particularly, on the simulation of a correlation model. The study has determined the nature of the information and communication technologies’ influence on production processes in the Russian regions. Furthermore, it has proved that the regional industry has significant reserves for further development. In particular, I discovered that there is an uneven rate of the information and communication development at the regional level. In most regions, measures are being taken to create a favourable environment ensuring interaction between authorities and enterprises, and production of competitive software compared with foreign analogues. Nevertheless, there is a number of problems including a low level of public access to the Internet and to the regions technological equipment, the regions’ digital divide, lack of the necessary regulatory framework. Thus, the proposed correlation model is an effective tool for analysing the regional industry’s development in the context of digitalization. Moreover, the model can be used as a management tool that allows assessing the effectiveness of the investments in information and communication technologies. The study’s results can contribute to the research and monitoring of the regional industry’s development, and identification of the resource requirements, which are necessary for the digital technologies’ introduction. These research findings can be applied for establishing the sectoral and integrated projects and industrial development programs.